Pengaruh Penggunaan ICT, Work Motivation dan WFB Sebagai Mediasi Terhadap Job Satisfaction ASN Pemerintahan Provinsi Jatim - Rini Ana Yacob (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study examines the effects of Information and Communication Technology (ICT) usage and work motivation on job satisfaction among civil servants (ASN) in the East Java Provincial Government, with work–family balance (WFB) as a mediating variable. The study is grounded in the growing integration of ICT in public services, which, despite its benefits, may generate technostress and disrupt employees’ work–life balance. Conversely, work motivation is viewed as a personal resource that can enhance both WFB and job satisfaction. A quantitative approach was employed using data from 80 purposively selected ASN respondents who actively use e-government systems such as SIPD, e-kinerja, and SIRUP. Data were analyzed through Structural Equation Modeling (SEM) using SmartPLS. The findings reveal that ICT usage has no significant direct or indirect effect (via WFB) on job satisfaction. In contrast, work motivation significantly and positively influences job satisfaction, both directly and indirectly through WFB. Moreover, WFB has a significant direct effect on job satisfaction. These results indicate that intrinsic individual factors and work–life balance play a more crucial role in enhancing job satisfaction than the intensity of ICT use. This study underscores the importance of psychological and contextual factors in public sector human resource management and highlights the need for policies that manage ICT demands while supporting employees’ work–life balance in the digital era.